Shear behaviour of masonry walls strengthened by external bonded FRP and TRC. (15th November 2015) - Bui, Thi-Loan; Si Larbi, A.; Reboul, N.; Ferrier, E.
Abstract: This experimental study focuses on the behaviour of hollow concrete brick masonry walls, especially walls reinforced with composite materials under in-plane loading conditions. This work is a step towards defining reliable seismic strengthening solutions. Indeed, in France, more stringent seismic design requirements for building structures have been considered with the replacement of old design codes. Thus, an experimental program has been performed at the laboratory scale. Six walls have been submitted for shear–compression tests – five walls are reinforced by (1) – fibre-reinforced polymer (FRP) strips using E-glass and carbon fabrics and/or (2) a textile-reinforced concrete (TRC), and the last wall acts as a reference. It is noted that the composite strips are mechanically anchored into the foundations of the walls to improve their efficiency. All of the walls share the same boundary and compressive loading conditions, which are representative of a seismic solicitation. Nevertheless, masonry wall performances and anchor efficiency are only evaluated under monotonic lateral loadings. A comparative study on global behaviour and on local mechanisms is performed and, in particular, highlights that the mechanical anchor systems play an important role in improving the behaviour of reinforced walls (by FRP and TRC) and that the solutions for strengthening by TRC permit the upgrade of the walls' ductility with a lower strength compared with the solutions with FRP.